The Influence of Investment, Local Original Income and Non-Oil and Gas Exports on Economic Growth - Burhanudin, Burhanudin; Darwati Susilastuti; Sugiyanto , Sugiyanto (PT. ALHAFI BERKAH INDONESIA, 2025)
The purpose of this study was to ascertain how local revenue, investment, and non-oil and gas exports affected economic growth. This study examines economic growth from 2014 to 2023 using data from 34 Indonesian provinces. The selection of the fixed effect model shows that economic growth is highly influenced by investment, local revenue, and non-oil and gas exports. Indonesia's economic recovery is highly dependent on investment in sectors that absorb a lot of labor, ease of business licensing, and security stability so that it can increase local revenue from regional taxes and regional levies. The government must encourage ease of doing business in the regions, reduce levies on mandatory services, regional taxation options between Provinces and Regencies/Cities, and new tax bases.